Risk Factors for Late HIV Presentation in Patients Treated at a Single Belgian Reference Centre from 2018 to 2022 - Damien Scaia; Karine Fombellida; Nathalie Maes; Majdouline El Moussaoui; Gilles Darcis (MDPI AG, 2024)
A late HIV diagnosis is associated with increased mortality and morbidity, increased healthcare costs and increased onward viral transmission. In this regard, we retrospectively analysed the characteristics of patients who presented for care at our centre from January 2018 to December 2022 to assess the proportion of patients and factors associated with late HIV presentation. We collected data from the Liège University Hospital database, and we used binary logistic regression models to analyse the impact of individuals' characteristics on late presentation. Among 167 participants, 38.3% were late presenters (LPs) (presenting for care with a CD4+ T-cell count < 350 cells/mm3 or after an AIDS-defining event), and 21.6% were late presenters with advanced disease (LPs-AD) (presenting for care with a CD4+ T-cell count < 200 cells/mm3 or after an AIDS-defining event). The risk of being an LPs-AD was increased in older individuals (OR on log-transformed age: 7.5) and individuals of sub-Saharan African origin compared to individuals of Belgian or other origin (ORs of 0.30 and 0.25, respectively). The results of this study suggest that broadening the focus beyond the previously common risk groups is essential to prevent late diagnosis.